Quantum Cascade Lasers - Stavrou, Vasilios N. (IntechOpen, 2017)
The book Quantum Cascade Lasers is divided into two sections. More specifically, in Section 1, the calculations on the band structure of cascade lasers and on the electronic band structure of QCL (e.g., transfer matrix technique, finite element method, and variational method, among others) under the existence of an applied electric field are presented. Moreover, a detailed investigation of electrical and optoelectronic properties of multiple-quantum-well structure is carried out. Furthermore, a theoretical study on the intensity noise characteristics of quantum-cascade lasers under the external noncoherent optical injection is carried out. This section ends with an important description on growth methods for QCLs and the possibility of developing GaN-based QCLs among other materials. A few applications of cascade laser structures like power amplification and THz applications are presented, among others, in Section 2. The THz QCL design and fabrication toward the high-temperature and large-average output power operations for the real applications are described. Furthermore, the importance of the power amplification and coherent combination techniques to improve the output power maintaining the single-mode operation is presented.